Persepsi Pelajar Institusi Pengajian Tinggi Awam (IPTA) Terhadap Kepentingan Pembangunan Hijau di Malaysia - Azmi, Muhammad Nur Fathi (Research in Management of Technology and Business, 2021)
The construction of stratified buildings in Malaysia is growing, especially in urban areas. However, most stratified buildings in Malaysia have not yet applied green development practices. This study is conducted to comprehend the basic concepts and the importance of green development application in Malaysia. This study also intends to identify the perceptions and level of awareness among students in public institutions of higher learning (IPTA) on green development in Malaysia. This study focuses on the selected IPTA students in Malaysia. The study uses the quantitative research approach by using questionnaires as the main data sources. The data involves a primary data from quantitative methods where a total of 112 IPTA students have participated in the questionnaire survey while the secondary data were obtained through data collection from website and journals. The results of the study have found that the awareness among selected IPTA students on green development in Malaysia are higher as they will be the next generation that will continue the development progress of Malaysia.